Imobilização de β-galactosidase produzida por bacillus licheniformis para aplicação em indústria láctea - Kuribayashi, Lilian Mayumi (2019)
In Brazil, there is no consensus about prevalence of lactose intolerance, although it is estimated to be between 40% and 60% of the population. In the last years, the food industry developed a wide range of lactose-reduced products aiming to allow the intolerant person to keep consuming dairy products. The lactose-reduced milk is produced with the enzyme β-galactosidase, which has the ability of breaking the lactose into glucose and galactose. Enzymes are expensive catalyzes and their use burdens the cost of the whole process. The retention of a biomolecule inside of a reactor or analytical system is called immobilization. The recover and reuse of enzymes through immobilized biocatalyzers makes the process affordable; so, the enzymatic immobilization has been considered the most promising method to turn the use of enzyme in large-scale more competitive. The aim of this work was the study of immobilization of β-galactosidase of Bacillus licheniformis in ion exchange resin. The immobilization process was tested in Duolite A568 and Amberlite XAD761 resins. The Duolite A568 showed better retention of the enzymatic activity and was chosen to be used at this study. The influence of enzyme concentration, duration and substrate presence in the immobilization process was tested previously. The best condition of immobilization was: 43 mL.L-1 of enzyme in the immobilization solution, 2 hours of reaction and the substrate didn’t improve the immobilized activity at this process. Then, the immobilization was evaluated in different buffers with diverse ionic strengths. The best result was obtained with BR 20 mM buffer because of its wide range of adjustable pH. A Central Composite Rotational Design (CCRD) was proposed to evaluate the immobilization process for the variables: enzymatic concentration, ionic strength and pH of the immobilization solution. The conditions that maximize the response are: ionic strength of 40 mM, pH 4.0 and enzymatic concentration of 43 mL.L-1. Then, the influence of multipoint attachment on the activity of immobilized enzyme was studied by using buffer solution pH 9.0 at 25oC for 24h. The influence of cross-linking through the use of glutaraldehyde in different concentrations as reticulant agent was also assessed. The stabilization step drastically impacted the activity of the immobilized enzyme, making the use of this step impossible at the experimental conditions of this study. The reticulation with different concentrations of glutaraldehyde showed significant influence on the activity of the immobilized enzyme; higher reagent concentrations (3.5 g.L-1) negatively impacted the enzymatic activity on the support, but showed stability of 92% and 69% related to number of uses in temperatures of reaction of 40oC and 5oC, respectively. On the other hand, the use of glutaraldehyde at lower concentrations (1.0 g.L-1) didn’t affect the activity of the immobilized enzyme and didn’t show good stability to the biocatalyzer, achieving the relative activity of 63% after 6 uses at 40oC and 48% after 3 uses at 5oC. At last, the storage tests for 36 days corroborated the theory that the use of glutaraldehyde as reticulant agent improves the stability of the immobilized biocatalyzer.